2018
DOI: 10.1002/cctc.201801373
|View full text |Cite
|
Sign up to set email alerts
|

One‐step Synthesis of Self‐standing Ni3S2/Ni2P Heteronanorods on Nickel Foam for Efficient Electrocatalytic Hydrogen Evolution over a Wide pH Range

Abstract: The development of efficient, stable and low‐cost electrocatalysts for hydrogen evolution reaction (HER) through a facile strategy is undoubtedly vital to realize sustainable production of H2 in water splitting but still challenging. Herein, we present a one‐step approach, a simultaneous phosphorization and sulfurization thermal treatment of NF at low temperature, to direct grow Ni‐S−P heteronanorod arrays consisting of Ni3S2 and Ni2P on nickel foam (Ni‐S−P NRs/NF). Due to the direct growth, one‐dimensional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…The XPS results confirmed that electronic interactions at the heterointerface of Ni 3 S 2 andN i x P y had become favorable to promotee lectrochemical activity,w hile V doping could also adjust the electronic structure of the catalyst, which couldo ptimize DG H* and DG H 2 O * and enhance hydrogen evolution efficiency. [38,46] Figure S7 (Supporting Information) shows that with increasing amount of NaH 2 PO 2 the Ni and SX PS signals of VNSP/NF clearly shift, that is, the amount of NaH 2 PO 2 is ac rucial factor in forming Ni x P y for electronic regulation of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XPS results confirmed that electronic interactions at the heterointerface of Ni 3 S 2 andN i x P y had become favorable to promotee lectrochemical activity,w hile V doping could also adjust the electronic structure of the catalyst, which couldo ptimize DG H* and DG H 2 O * and enhance hydrogen evolution efficiency. [38,46] Figure S7 (Supporting Information) shows that with increasing amount of NaH 2 PO 2 the Ni and SX PS signals of VNSP/NF clearly shift, that is, the amount of NaH 2 PO 2 is ac rucial factor in forming Ni x P y for electronic regulation of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al. designed a 1D Ni 3 S 2 /Ni 2 P material coated on nickel foam (NF) as an efficient electrocatalyst to improve the HER [46] . They proposed that the outstanding HER activity at all pH values was due to the strong coupling effect between two‐phase interfaces, which regulated Δ G H* and Δ G normalH2normalO* .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pH‐dependent characteristics of most electrocatalysts restrict the large‐scale practical applications of HER because different electrochemical water splitting systems always require the electrolytes with specific pH values . All the above‐mentioned facts have put forward an urgent demand for the design of non‐noble hydrogen‐evolving electrocatalysts capable of high efficiency, favorable price, superior stability and wide pH adaptability …”
Section: Introductionmentioning
confidence: 99%
“…[9,10] All the above-mentioned facts have put forward an urgent demand for the design of non-noble hydrogen-evolving electrocatalysts capable of high efficiency, favorable price, superior stability and wide pH adaptability. [11,12] Up to now, enormous achievements in the field of noble metal-free HER electrocatalysts have been made and they can be summarized as follows: (1) transition metal borides (TMBs) consisting of Mo 2 B 4 , [13] MoB, [14] NiÀ B alloy; [15] (2) transition metal dichalcogenides (TMDs) involving MoS 2 , [16] WS 2 , [17] MoTe 2 and MoSe 2 , [18] CoS 2 ; [19] (3) transition metal nitrides (TMNs) containing Mo 2 N, [20] WN, [21] Ni 3 N; [22] (4) transition metal carbides (TMCs) such as MoC x and WC x , [23] Ni 3 C, [24] Ni 3 Mo 3 C [25] and (5) transition metal phosphides (TMPs) including CoP, [26] FeP, [27] Ni 2 P, [28] MoP, [29] WP. [30] Among aforementioned alternatives, on-going endeavors have been devoted to the nickel phosphide-type TMPs, in sight of the merits of favorable catalytic activity, costeffective, earth abundance and excellent longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Zhou et al . have observed that Ni 3 S 2 /Ni 2 P NA exhibits enhanced stability and activity for HER.…”
Section: Constructing Earth‐abundant 3d Nanoarrays For Efficient Overmentioning
confidence: 99%